2015
DOI: 10.1055/s-0035-1559684
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Bromocriptine-QR in Type 2 Diabetes: A Systematic Review and Meta-Analysis

Abstract: Bromocriptine-QR (quick release) is a novel treatment for type 2 diabetes. The objective of this study is to assess the efficacy and safety of bromocriptine-QR in adults with type 2 diabetes mellitus based on randomized controlled trials published in peer-reviewed journals or as abstracts. We performed a comprehensive literature search of MEDLINE, Pubmed, Web of Science, EMBASE, and the Cochrane Library up to May 2015. Randomized controlled trials of bromocriptine-QR therapy in type 2 diabetes mellitus were el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 42 publications
(109 reference statements)
1
25
0
Order By: Relevance
“…Bromocriptine QR was weight neutral and was not associated with the risk of hypoglycaemia, hypotension or cardiovascular effects 348 . However, bromocriptine QR increased gastrointestinal adverse effects of nausea and vomiting, relative to placebo 348 . In an RCT 349 involving 3,095 patients, bromocriptine QR (as monotherapy or add-on to glucoselowering agents, including insulin) was shown to reduce the risk of cardiovascular disease, compared with placebo (HR 0.60, 95% CI 0.35-0.96) by 52 weeks.…”
Section: Other Agents Dopamine D 2 Receptor Agonistsmentioning
confidence: 87%
See 1 more Smart Citation
“…Bromocriptine QR was weight neutral and was not associated with the risk of hypoglycaemia, hypotension or cardiovascular effects 348 . However, bromocriptine QR increased gastrointestinal adverse effects of nausea and vomiting, relative to placebo 348 . In an RCT 349 involving 3,095 patients, bromocriptine QR (as monotherapy or add-on to glucoselowering agents, including insulin) was shown to reduce the risk of cardiovascular disease, compared with placebo (HR 0.60, 95% CI 0.35-0.96) by 52 weeks.…”
Section: Other Agents Dopamine D 2 Receptor Agonistsmentioning
confidence: 87%
“…The drug provides a morning boost to hypothalamic dopamine levels, consistent with normal diurnal glucoregulation, and contributing to a reduction of sympathetic tone, neural suppression of hepatic glucose production and improvement in peripheral glucose disposal, without affecting insulin levels 28,344,346,347 . A meta-analysis showed that bromocriptine QR add-on therapy, compared with placebo, reduced levels of HbA 1c (−6.52 mmol/mol, 95% CI −8.07 mmol/mol to −4.97 mmol/mol) and FPG (−1.04 mmol/l, 95% CI −1.49 mmol/l to −0.59 mmol/l), but had no effect on postprandial glucose 348 . Bromocriptine QR was weight neutral and was not associated with the risk of hypoglycaemia, hypotension or cardiovascular effects 348 .…”
Section: Other Agents Dopamine D 2 Receptor Agonistsmentioning
confidence: 99%
“…Lastly, it should be appreciated that bromocriptine-QR is administered once daily in the morning and provides only a brief 4-5-h rise in plasma bromocriptine level [162] whereas multiple daily doses of bromocriptine are typically used to treat prolactinoma and Parkinson's disease that consequently may raise the plasma bromocriptine level chronically over the entire day each day. No cases of cardiac valvulopathy have been reported in any clinical studies to date with bromocriptine-QR therapy [204].…”
Section: Clinical Use and Treatment Considerations Summarymentioning
confidence: 99%
“…The D2-like receptors inhibit adenylyl cyclase and are the targets for most of the common drugs used to treat Parkinson's disease. Bromocriptine (BRO) is a D2 agonist that inhibits PRL production and release, and is used in the management of prolactinomas (Seeman and Van, 1994), to treat type 2 diabetes (Liang et al, 2015) and for the suppression of lactation Neuropeptides xxx (2016) xxx-xxx (Verma et al, 2006;Bernard et al, 2015). In addition, dopamine has not only been used to treat shock in adults, but also in neonates (Noori and Seri, 2012;Saini et al, 2014), who have more plastic, therefore susceptible, dopaminergic neurons than adults.…”
Section: Introductionmentioning
confidence: 99%